Systemic Sclerosis - Radic, Mislav (IntechOpen, 2017)
Systemic sclerosis is a rare autoimmune disease characterized by immunological alterations, small vessel vasculopathy, and skin and other organ fibrosis. Despite progress in the knowledge of pathogenic steps and therapeutic options, when compared with other rheumatic conditions, it shows the lowest life expectancy rate. Early diagnosis is important as early treatment could lead to better outcomes. Great progress has been made in the treatment of specific symptoms; however, there are still no disease-modifying drugs that are able to control the overall disease activity satisfactorily. This book covers the latest knowledge in systemic sclerosis from pathophysiology to clinical presentation and management. Hopefully, this book will be a useful resource to students, residents, rheumatologists, dermatologist, and anyone interested in this fascinating disease.